2017
DOI: 10.1016/j.dld.2017.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Value of cross-sectional imaging in assessing active Crohn’s disease before stoma reversal

Abstract: Cross-sectional imaging revealed postoperative recurrence in about a quarter of patients before stoma reversal; this finding may influence the postoperative treatment strategy and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…However, there is little experience in the criteria for VEO-IBD stoma closure. [39][40] This study found that ileostomy accounted for more than 90% of all VEO-IBD children, and the reasons may be as follows: VEO-IBD is mainly CD, and CD mostly involves the ileocecal region. The treatment strategy has gradually changed from passive palliative care to active comprehensive management, and the need for surgical intervention is higher.…”
Section: Discussionmentioning
confidence: 92%
“…However, there is little experience in the criteria for VEO-IBD stoma closure. [39][40] This study found that ileostomy accounted for more than 90% of all VEO-IBD children, and the reasons may be as follows: VEO-IBD is mainly CD, and CD mostly involves the ileocecal region. The treatment strategy has gradually changed from passive palliative care to active comprehensive management, and the need for surgical intervention is higher.…”
Section: Discussionmentioning
confidence: 92%
“…When the length of the ileocolic segment of CD on pathological examination was ≤20 cm, the mean (SD) length on MRE was 10 (13.5) cm. When the length on pathological examination was between 20 and 40 cm, the mean (SD) length on MRE was 14 (10) cm. When the length on pathological examination was >40 cm, the mean (SD) length on MRE was 18 (13) cm.…”
Section: Correlation Between Radiological and Pathological Measurementsmentioning
confidence: 99%
“…9 Surgical strategy and approach are correctly predicted by MRE in patients with CD. 8,10 When surgery is indicated in primary, stricturing, and localized CD of the small bowel, the European Crohn's and Colitis Organization (ECCO) surgical guidelines have stressed the importance of evaluation of the affected segment length to assess feasibility of surgery. 11 Only 1 study investigated the accuracy of imaging for measurement of the length of the ileocolic segment affected by CD.…”
mentioning
confidence: 99%